2015
DOI: 10.1111/plb.12345
|View full text |Cite
|
Sign up to set email alerts
|

Survey of duckweed diversity in Lake Chao and total fatty acid, triacylglycerol, profiles of representative strains

Abstract: Lemnaceae (duckweeds) are widely distributed aquatic flowering plants. Their high growth rate, starch content and suitability for bioremediation make them potential feedstock for biofuels. However, few natural duckweed resources have been investigated in China, and there is no information about total fatty acid (TFA) and triacylglycerol (TAG) composition of duckweeds from China. Here, the genetic diversity of a natural duckweed population collected from Lake Chao, China, was investigated using multilocus seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 45 publications
3
22
0
Order By: Relevance
“…The results showed that strains representing L. aequinoctialis and S. polyrhiza were predominant, which was similar to duckweed diversity in Lake Chao (Tang et al . ). Subsequently, 20 duckweed strains were further investigated to assess best growth performance (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that strains representing L. aequinoctialis and S. polyrhiza were predominant, which was similar to duckweed diversity in Lake Chao (Tang et al . ). Subsequently, 20 duckweed strains were further investigated to assess best growth performance (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we found that the contribution of PUFA was 60% or higher for all analyzed Wolffia species, except for W. globosa 9498 (~54.5% PUFA). Tang et al ( 2015 ) investigated the fatty acid contents of the four species, Spirodela polyrhiza, Landoltia punctata, Lemna aequinoctialis , and W. globosa isolated from the lake Chao, China. Yan et al ( 2013 ) reported the most comprehensive survey of fatty acids in duckweeds by investigating 30 species (one clone per species) including eight species of Wolffia .…”
Section: Discussionmentioning
confidence: 99%
“…Samples isolated from four locations were genotyped using two chloroplast markers and nuclear ribosomal DNA markers. The chloroplast DNA markers identified the samples as the greater duckweed, Spirodela polyrhiza , a dominant duckweed species in southern and middle China (Tang et al, 2015 ). The chloroplast ATP barcode showed some variability between samples, characteristic for the sequence variation between ecotypes of the same species (Supplement Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%